Training on the Utilization of the HVSR Geophysical Method Based on the Concept of Mechanical Wave Propagation for Earthquake Hazard Potential Analysis in Kuto Rejo Village - Hadi, Arif Ismul; Refrizon; Muda Lubis, Ashar; Johan, Septi; Halauddin (Indonesian Journal of Community Empowerment and Service (ICOMES), 2025)
Kepahiang Regency has a high potential for earthquake hazards. This is because the Kepahiang area is located in the subduction zone of the Indo-Australian tectonic plate movement in the ocean and the movement of the Musi segment of the Sumatra fault on land as the main fault. As an area with high earthquake hazard potential and its location near the Musi segment fault, efforts are needed to reduce the risk of disasters due to earthquakes through the activity "Training on the Utilization of the Horizontal to Vertical Spectral Ratio (HVSR) Geophysical Method”. The HVSR method is a geophysical method based on the concept of mechanical wave propagation. HVSR measurements can be used to understand the structural properties of subsurface. The target audience for this activity is Village Apparatus and Residents of Kuto Rejo Village, Kepahiang Regency. This activity aims to provide an understanding of the basic concepts of mechanical wave propagation in rocks and provide training in the use of the HVSR method. The method used is through the stages of focus group discussion (FGD), field data acquisition, processing, interpretation and evaluation. The indicator of the achievement of the objectives of this activity is if each activity participant can acquisition, process, analyze, and interpret and answer the questionnaire related to the community service material correctly. The results of this activity provide insight into the importance of local wisdom-based earthquake hazard mitigation for disaster risk reduction. Village Apparatus and Residents of Kuto Rejo Village will continuously share their knowledge with other villagers from this activity.